Food price instability in developing countries. The need for public intervention to stabilise prices - Galtier, Franck (Perspective, 2009)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":" The food crises which affected the Sahel in 2005 and the international markets in 2008 have placed the issue of food price instability at the very forefront of discussion. The urban riots which broke out in about forty developing countries as a result of the sharp price increases of 2008 emphasised the fact that this instability can have serious consequences for food security both in the short term – consumer access to food – and in the long term – incentive to producers to invest and increase production. Numerous experts predict that this instability will be long-lasting, both on the international markets and in developing countries. What, then, should be done?"}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}"> Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":" The food crises which affected the Sahel in 2005 and the international markets in 2008 have placed the issue of food price instability at the very forefront of discussion. The urban riots which broke out in about forty developing countries as a result of the sharp price increases of 2008 emphasised the fact that this instability can have serious consequences for food security both in the short term – consumer access to food – and in the long term – incentive to producers to invest and increase production. Numerous experts predict that this instability will be long-lasting, both on the international markets and in developing countries. What, then, should be done?"}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">The food crises which affected the Sahel in 2005 and the international markets in 2008 have placed the issue of food price instability at the very forefront of discussion. The urban riots which broke out in about forty developing countries as a result of the sharp price increases of 2008 emphasised the fact that this instability can have serious consequences for food security both in the short term – consumer access to food – and in the long term – incentive to producers to invest and increase production. Numerous experts predict that this instability will be long-lasting, both on the international markets and in developing countries. What, then, should be done?